Clinical Use of Dostarlimab in Advanced Stage and Recurrent Endometrial Cancer: Patient Selection and Perspectives - Bujnak AC; File B; Tewari KS (Cancer Management and Research)
Alyssa C Bujnak,1 Brittany File,2 Krishnansu S Tewari1 1Department of Gynecologic Oncology, University of California, Irvine-Medical Center, Orange, California, USA; 2Department of Obstetrics and Gynecology, University of California, Irvine-Medical Center, Orange, California, USACorrespondence: Alyssa C Bujnak, University of California, Irvine-Medical Center, 3800 West Chapman Avenue, Suite 3400, Orange, CA, USA, Tel +1 714 456-8888, 92868, Fax +1 714 509-2257, Email abujnak@hs.uci.eduAbstract: Endometrial cancer (EC) is the most common gynecologic cancer in developed nations with reported 420,368 new cases worldwide in 2022 and resulting in 97,723 deaths that year; it is also one of the few cancers with expected increases in incidence and mortality, which are expected to increase by 50% and 70%, respectively, by 2045. The mortality from EC can largely be attributed to the advanced stage and recurrent cases. Over the past decade, the standard of care for treatment of primary advanced stage and recurrent EC has been chemotherapy, resulting in a median overall survival (OS) of less than 3 years. Advances in molecular tumor profiling have highlighted that a portion of EC tumors release high levels of neoantigens, indicating an opportunity to harness the immune system in therapeutic strategies. On August 1st, 2024, the United States Food and Drug Administration expanded the indication of the immunologic anti-PD-1 checkpoint inhibitor, dostarlimab, and chemotherapy in endometrial cancer. This review summarizes the rationale, evidence, and indications for the use of dostarlimab in advanced and recurrent endometrial cancer.Keywords: dostarlimab, pembrolizumab, durvalumab, endometrial cancer, mismatch repair deficiency, PD-1 inhibition, immune checkpoint inhibitor